Effects of competition and egg predation on shelter use by Octopus tehuelchus females - Narvarte, Maite Andrea (2013)
Parental care in the ocean ranges from provision to eggs and embryos to protection from predators. In particular, nest attendance has several benefits associated with relatively higher survival rates, lower vulnerability to predation and parasitism, and faster development rates. The quality of shelters matters, and adults of many species have to compete for suitable shelters. Here, we studied whether shelter type for brooding and egg protection from predation could be a determinant of competition among adults in the cephalopod Octopus tehuelchus. To this end, we (1) assessed the abundance of different types of shelters and preference under field and laboratory conditions, (2) tested the effect of intraspecific competition for shelters, (3) estimated density of potential sources of embryo mortality, and (4) determined the role of female protection in egg survival against predators. We found that in areas where shelters for development are scarce, females compete with males for the most suitable shelters. Fecundity depends on the female size, and shelters with higher volume are preferably selected by females. Excluding the brooding female from shelters resulted in increased egg mortality due to predation by octopus males and removal by chitons. We suggest that, in this species, shelter availability poses a constraint to brooding and affects total parental investment in reproduction and predation risk on eggs. This constraint may also take place in other marine invertebrates with similar life history traits, especially in areas where shelter is limited.